Transverse instability of a bunched beam with space charge and wakefield - V. Balbekov (Physical Review Special Topics. Accelerators and Beams, 2011)
Transverse instability of a bunch in a ring accelerator is considered with space charge and wakefield taken into account. It is assumed that space charge tune shift significantly exceeds the synchrotron tune. Bunch spectrum, instability growth rate, and effects of chromaticity are studied with different bunch and wake forms. Fast instability caused by coupling of transverse modes is studied in detail. It is shown that, for monotonic wakes, the transverse mode coupling instability is possible only with a certain sign of the wake. Its threshold and growth rate are calculated precisely over a wide range of parameters.